Atypical idiopathic inflammatory demyelinating lesions: Prognostic implications and relation to multiple sclerosis - Wallner-Blazek, M; Rovira, A; Fillipp, M; Rocca, M; Miller, D; Schmierer, K; Frederiksen, J; Gass, A; Gama, H; Tilbery, C; Rocha, A; Flores, J; et al. (2013)
Atypical lesions of a presumably idiopathic inflammatory demyelinating origin present quite variably and may pose diagnostic problems. The subsequent clinical course is also uncertain. We, therefore, wanted to clarify if atypical idiopathic inflammatory demyelinating lesions (AIIDLs) can be classified according to previously suggested radiologic characteristics and how this classification relates to prognosis. Searching the databases of eight tertiary referral centres we identified 90 adult patients (61 women, 29 men; mean age 34 years) with ≥1 AIIDL. We collected their demographic, clinical and magnetic resonance imaging data and obtained follow-up (FU) information on 77 of these patients over a mean duration of 4 years. The AIIDLs presented as a single lesion in 72 (80 %) patients and exhibited an infiltrative (n = 35), megacystic (n = 16), Baló (n = 10) or ring-like (n = 16) lesion appearance in 77 (86 %) patients. Additional multiple sclerosis (MS)-typical lesions existed in 48 (53 %) patients. During FU, a further clinical attack occurred rarely (23-35 % of patients) except for patients with ring-like AIIDLs (62 %). Further attacks were also significantly more often in patients with coexisting MS-typical lesions (41 vs. 10 %, p < 0.005). New AIIDLs developed in six (7 %), and new MS-typical lesions in 29 (42 %) patients. Our findings confirm the previously reported subtypes of AIIDLs. Most types confer a relatively low risk of further clinical attacks, except for ring-like lesions and the combination with MS-typical lesions. © 2013 Springer-Verlag Berlin Heidelberg.